Assessment of the Effectiveness of Video Assisted Teaching Program on Knowledge and Practice Regarding Oral Hygiene Among Preschool Children at a Selected Primary School in Vellore - Elizabeth Rani; Clement I; Nisha Clement (RGUHS Journal of Nursing Sciences)
Background and objective Dental caries is one of the most common health problems affecting children. Dental exam is recommended in the school health program at least once a year. Nurses take part in teaching parents kids and teachers about oral hygiene. However it has never been demonstrated that sloppy teeth brushing can stop dental cavities. The effectiveness of plaque removal depends on the type of toothbrush used. This study aimed to assess the knowledge and practice regarding oral hygiene among preschool children pre and post intervention of a video-assisted program regarding oral hygiene.Methodology A quantitative research approach was adopted for this study. Quasi-experimental design was used in the study to assess the effectiveness of video-assisted teaching program on knowledge and practice regarding oral hygiene among preschool children at a selected school in Vellore. The study was conducted including 60 pre-school children from pre-K.G L.K.G U.K.G children from Susanrsquos kinder garden school Vellore. The researcher selected subjects who fulfilled the inclusion criteria using random sampling. The subjects were interviewed using a semi structured questionnaire to assess the knowledge and an observational checklist to assess the practice regarding oral hygiene and Fones brushing technique. Post test was conducted after one week.Results In the experimental group the mean pre-test score was 7.3 with a standard deviation of 2.8 while the mean post-test score was 15.7 with a standard deviation of 2.12 in the experimental group. The average disparity was 8.4. At the 0.05 level the obtained t value of 14.8 was highly significant. The estimated t value was the same as the mean pretest practice score of 3.4 with SD 1.4 and the post-test practice score of 8.3 with SD 2.9 the calculated t value was 17.5 which was highly significant at p lt0.05 level. There was a significant difference between the mean pre-and post-test levels of knowledge and practice among preschool children in the experimental group. Thus the video assisted teaching program was effective in improving the levels of knowledge and practice among preschool children in the experimental group.Conclusion The brushing methods used were least efficient according to this study. Training in oral hygiene should be based on a childs motor skill level and developmental stage. It is crucial to consider variations in tooth-brushing abilities especially in younger children. Each child needs intense customized training to achieve the techniques desired effects.